Sosialisasi Penyelenggaraan Rekam Medis Di Klinik Prima Husada Kota Bandung - Tedy Hidayat; Nuke Dewi Utami Hamid; Jajat Sudrajat; Syaikhul Wahab; Desy Widyaningrum; Santy Christinawati; Erix Gunawan; Ai Susi Susanti; Shinta Elvira (PADMA, 2023)
Primary clinics play an essential role as first-level healthcare facilities that provide both medical and administrative services to the community. In efforts to improve the quality of healthcare services, the management of medical records serves as one of the main components that must be carried out in an orderly, accurate, and systematic manner. Medical records function not only as patient documentation but also as legal documents, communication tools among healthcare professionals, and data sources for service quality evaluation. This Community Service (PKM) activity was conducted at Klinik Prima Husada, Bandung City, with the aim of strengthening staff understanding of proper procedures for organizing and completing medical records. The methods included socialization, education, and mentoring sessions involving healthcare and administrative personnel. Based on the implementation results, the medical record system has been functioning but still faces challenges, particularly in diagnosis coding and form completeness. Through this activity, it is expected that the staff’s knowledge and skills in managing medical records will improve, thereby supporting work efficiency, administrative orderliness, and the overall quality of healthcare services within the clinic.